(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The aim of this paper is to analyze the relationship between artificial intelligence and evidential reasoning in the criminal trial. Firstly, we provide some examples of the artificial intelligence’ impact on the conceptual foundation of evidence. Subsequently, the attention is focused on the framework governing automated decisions issued in the criminal trial. Finally, after examining the role of artificial intelligence tools in the different epistemological contexts of the judicial proceeding (context of research, discovery and justification), we carry out a review about some models of man-machine collaboration for the fact-finding process.